Upaya menjaga kesehatan ibu hamil di masa pandemi COVID-19 - Syifa, Syifa; Martadiansyah, Abarham; Kusuma, Hadrians; Kurniati, Ardesy Melizah; Fatimah , Nyimas (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2021)
The early 2021 rise in COVID-19 cases, as well as the advent of novel types due to mutations, tightened social activities. To avoid transmission of the virus between pregnant women, health workers, and other visitors, service adjustments are required to assist pregnant women in doing prenatal checkups. Every day at home, efforts to maintain the maternal can be made, including normal physical activity and managing dietary intake. To boost pregnant women's understanding, community service activities such as counseling on antenatal care, physical exercise, and particular dietary intake are carried out. In total, 92 expectant mothers took part in webinars. Prior to the webinar, a pretest was used to measure initial knowledge; the average result was in the "Good" category. The activity went off without a hitch, and the attendees were eager to ask questions. The post-test score increased to the "Very Good" level, according to the evaluation data. This webinar activity will help pregnant women gain a better understanding of how to stay healthy during the COVID-19 pandemic.